Caracterización de la logística en la cadena de suministro de cosméticos y productos de aseo - Orjuela-Castro, Javier Arturo; Diaz-Rios, Oscar Javier; Gonzalez-Perez, Angelo Yoed (Revista Científica, 2017)
The sector of cosmetics and toiletries is a world class sector, consolidated in Colombia with 690 companies of which 420 are in Bogotá D.C. Taking into account that logistics management generates competitive advantage in organizations as factor of success in a global economy, this paper proposes a logistics analysis applied to the case of cosmetics and toiletries supply chain. The results include the diagnosis of logistics processes and resources, which they were studied with an own methodology proposal. The methodology allowed study the logistics factors and variables, elements that recognized the logistical behaviour in the different links of the supply chain.